A Comparative Study of Impacts of Single-dose Systemic Methotrexate and Salpingectomy Surgery Treatments on Ovarian Reserve in Women with Ectopic Pregnancy Using Anti-Mullerian Hormone - Askari, Elham (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: Ectopic pregnancy (EP) is a serious cause of maternal mortality that complicates about 2% of pregnancies. There are two approaches for EP treatments including surgical intervention and methotrexate (MTX). The present study aims to comparatively investigate impacts of single-dose MTX and laparoscopic salpingectomy treatments on ovarian reserve in women with EP using anti-Mullerian hormone (AMH) level as the biomarker of subsequent pregnancy. Materials and Methods: This was a prospective randomized clinical trial conducted on 30 patients with EP who referred to two University Hospitals in Shiraz during December 2014–June 2016. The subjects were divided into single-dose MTX group and salpingectomy group. Before the treatments and at 6-month post-treatment follow-up, the serum AMH level was measured using ELIZA method and compared within and between groups. Results: The serum AMH level significantly decreased in both groups at 6-month post-treatment compared with the baseline levels (P = 0.05). The single-dose MTX group showed more reduction than the surgery group (1.6 vs. 1.2 pg/mL). However, the difference in the post-treatment serum AMH level was not statistically significant between the two groups (P > 0.05). Conclusion: Both single-dose MTX group and salpingectomy treatments are effective for EP. For patients with less severe EP, it is recommended to administer single-dose MTX than surgical approach.